The Impact Of Viral Content On Public Policy: A Systematic Literature Review On Institutional Responses To Online Public Aspirations - Abadi, Yudha Budi; Thahir, Andi; Fitri, Tin Amalia (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2024)
This systematic literature review explores the growing phenomenon of viral news and its influence on judicial processes, focusing on how institutions respond to public aspirations voiced through online media. The study aims to identify the mechanisms through which viral news affects trial outcomes and institutional decision-making, while also examining the societal and legal implications of this trend. Using a mixed-methods approach, the research synthesizes data from the last five years to analyze patterns, gaps, and theoretical frameworks. Preliminary findings suggest that viral news amplifies public pressure, often leading to accelerated or altered judicial responses. The study contributes to the theoretical understanding of media influence on legal systems and offers policy recommendations for balancing public aspirations with judicial integrity. By addressing the intersection of media, law, and public opinion, this research holds significant implications for policymakers, legal practitioners, and media scholars.